Mitral Regurgitation and Body Mass Index Increase the Predictability of Perioperative Bleeding in Anticoagulated Patients With Nonvalvular Atrial Fibrillation - Huang, Hao; Cai, Chi; Hua, Wei; Zhang, Nixiao; Niu, Hongxia; Chen, Xuhua; Wang, Jing; Jia, Yuhe; Chu, Jianmin; Tang, Min; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2022)
Background: Catheter Ablation effectively restores sinus rhythm in atrial fibrillation (AF), but causes a short-term fluctuation in coagulation state. Potential risk factors and better management during this perioperative period remain understudied. Methods: We consecutively included 940 non-valvular AF patients who received catheter ablation (CA) in Fuwai Hospital, Beijing, China. Patients were divided into two groups according to their bleeding status during three months’ anticoagulation. Any adverse events related to bleeding in three months were evaluated. HAS-BLED score and ABC-bleeding score, as well as other potential factors, were explored to predict bleeding risk. Results: In this observational study, 8.0% and 0.9% of the whole population suffered from bleeding and thromboembolic events, respectively. After adjusting for known factors related to bleeding, mitral regurgitation (MR, p for trend<0.001) and body mass index (BMI, OR=0.920, 95% CI: 0.852-0.993, p=0.033) were the most significant ones. C-indexes of the HAS-BLED score and ABC-bleeding score for bleeding were 0.558 (0.492-0.624) and 0.585 (0.515-0.655), respectively. The incorporation of MR and BMI significantly improved the predictive value based on HAS-BLED score (c-index=0.650, 95%CI: 0.585-0.715, p=0.004) and ABC-bleeding score (c-index=0.671, 95%CI :0.611-0.731, p<0.001). The relative risk of mild-moderate MR was 4.500 (95% CI: 1. 625-12.460) in AF patients with HAS-BLED=1 and 4.654 (95% CI: 1.496-14.475) in HAS-BLED≥2, while was not observed in patients with HAS-BLED=0 (p=0.722). Conclusion: More severe mitral regurgitation and lower body mass index are associated with a higher incidence of perioperative bleeding, which helps improve the predictability of increased individual bleeding risk of a patient with non-valvular AF who has received catheter ablation therapy and oral anticoagulants.